Wild vertebrate roadkill in northern Central America: a first assessment using citizen science data - Arévalo-Ayala, Diego J; Funes, Guillermo; Escobar-Anleu, Bárbara I.; Funes, Carlos (Cambridge University Press, 2025)
Roads are vital for the economic development of countries but they pose major problems for wildlife. The road network in Central America is expanding, yet information about wildlife–vehicle collisions is scarce. We compiled data on vertebrate collisions with vehicles in Guatemala, El Salvador and Honduras, from projects created on the citizen science platform iNaturalist, to provide the first assessment of how these species are affected by roads in northern Central America. Our projects gathered 670 wildlife roadkill records that had been logged by 95 users across the three countries, with 122 species identified. Mammals and reptiles represented 44 and 30% of the records, respectively, with opossums Didelphis spp. and Philander vossi, the common boa Boa constrictor and the neotropical whip snake Masticophis mentovarius being the most frequently reported species (112, 28, 43 and 23 records, respectively). One of the species recorded is categorized as globally Endangered on the IUCN Red List, two as Vulnerable, four as Near Threatened and four have not been evaluated. Forty-six species are listed as Threatened or Endangered nationally. This study is the first roadkill assessment in northern Central America to which both members of the public and specialists contributed, underscoring the value of public engagement and citizen science. We urge further assessment of road impacts on wildlife in this region using standardized methods to identify roadkill rates and hotspots, and the implementation of mitigation measures for existing and planned roads in the region.